2016
DOI: 10.3945/an.115.010405
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Small Intestine in Developmental Programming: Impact of Maternal Nutrition on the Dam and Offspring

Abstract: Small-intestinal growth and function are critical for optimal animal growth and health and play a major role in nutrient digestion and absorption, energy and nutrient expenditure, and immunological competence. During fetal and perinatal development, the small intestine is affected by the maternal environment and nutrient intake. In ruminants, altered small-intestinal mass, villi morphology, hypertrophy, hyperplasia, vascularity, and gene expression have been observed as a result of poor gestational nutrition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 76 publications
1
52
0
1
Order By: Relevance
“…Various studies have reported the effect of nutritional programming on organ development during the fetal period including muscle and small intestine [ 34 , 35 ]. The number of muscle fibers is determined during the fetal period and there is little net increase after birth underscoring the importance of the fetal period on skeletal muscle [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the effect of nutritional programming on organ development during the fetal period including muscle and small intestine [ 34 , 35 ]. The number of muscle fibers is determined during the fetal period and there is little net increase after birth underscoring the importance of the fetal period on skeletal muscle [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lambs born to dams fed E+ seed during MID gestation had lower weights of the proximal jejunum section. Reductions in weight are generally associated with reductions in villus and crypt density, which suggest a reduction in functional area in the small intestine [ 35 ]. Wang and co-workers [ 36 ] also noted reductions in small intestine weights of IUGR piglets that were associated with reduced mucosal mass, malabsorption of nutrients, proteolytic activity and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of maternal nutrition on the size and function of the digestive tract are considerable because of their potential effects on the availability of nutrients to the offspring during pre‐ and post‐ natal phases. Overall, sheep and rat fetuses that suffered from intrauterine growth restriction are born with immature SI, with lower villus height and crypt depth, suggesting smaller functional area (Meyer & Caton, ; Trahair, DeBarro, Robinson, & Owens, ). On the other hand, studies in cattle demonstrate greater SI length and villi length in fetuses from restricted dams (Duarte et al, ).…”
Section: Discussionmentioning
confidence: 99%